3D-modeling of the formation of harmful components the combustion of pulverized coal dust in the volume of the combustion chamber of the boiler BKZ-75 Shakhtinskaya CHP - Аскарова, А.С.; Болегеновa, С.A.; Мaксимов, В.Ю.; Aлдияровa, A.Н. (Recent Contributions to Physics, 2016)
The study aims to examine the formation of harmful components during the combustion of pulverized coal dust in the volume of the combustion chamber of the boiler BKZ-75 Shakhtinskaya СHP. Based on the numerical solution of the system of equations of convective heat and mass transfer, taking into account the kinetics of chemical reactions, two-phase flow, nonlinear effects of convection and radiation heat transfer methods and three-dimensional modeling, it is necessary to identify the formation of carbon monoxide gas throughout the volume of the combustion chamber, in its main sections and at the exit. The research results will be used to generate recommendations for optimization of existing technologies for burning low-grade coal fuel to Kazakhstani fields, with the aim of improving process efficiency by burning fuel in real power plants with the most efficient energy and minimal harmful impact on the environment.